INTEGRATION OF ISLAMIC CHARACTER EDUCATION IN MERDEKA BELAJAR CURRICULUM - Amiq, Bahrul; Muhith, Abd.; Masud, Masud; Zainudin, Agus (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
Islamic character education is an effort to build a generation that has noble morals based on Islamic values. The Merdeka Belajar Curriculum initiated by the Indonesian government provides flexibility for educators to integrate local values, including religious values, into learning. This article aims to analyze how Islamic character education can be integrated in the Merdeka Belajar Curriculum. This research uses a qualitative descriptive approach through literature review. The results show that the integration of Islamic character education requires collaboration between educators, curriculum, and society in supporting the creation of religious, ethical, and accomplished students. In conclusion, Islamic character education is a key element in building holistic education according to the demands of the modern era.